PRIMAS: a real-time 3D motion-analysis system - Sabel, J. C.; van Veenendaal, H. L.; Furnee, E. H. (Proceedings of SPIE, 1994)
The paper describes a CCD TV-camera-based system for real-time multicamera 2D detection of retro-reflective targets and software for accurate and fast 3D reconstruction. Applications of this system can be found in the fields of sports, biomechanics, rehabilitation research, and various other areas of science and industry. The new feature of real-time 3D opens an even broader perspective of application areas; animations in virtual reality are an interesting example. After presenting an overview of the hardware and the camera calibration method, the paper focuses on the real-time algorithms used for matching of the images and subsequent 3D reconstruction of marker positions. When using a calibrated setup of two cameras, it is now possible to track at least ten markers at 100 Hz. Limitations in the performance are determined by the visibility of the markers, which could be improved by adding a third camera.